2017
DOI: 10.1093/toxsci/kfx144
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Triptolide-Induced Hepatotoxicity by Imaging and Transcriptomics in a Novel Zebrafish Model

Abstract: Triptolide is a vine extract used in traditional Chinese medicines and associated with hepatotoxicity. In vitro data suggest that inhibition of RNA synthesis may be the mechanism of toxicity. For studying drug-induced liver injury the zebrafish has experimental, practical and financial advantages compared with rodents. The aim of this study was to explore the mechanism of triptolide toxicity using zebrafish as the model system. The effect of triptolide exposure on zebrafish larvae was determined with regard to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…It was reported that TP has antiangiogenic (He et al, ), antiproteinuric (Wang et al, ) and antitumor (Gao et al, ) activities in the zebrafish. It has also been reported that exposure to TP was dose‐dependent for mortality, hepatocyte vacuolation, disarray and oncotic necrosis in zebrafish (Vliegenthart et al, ). It has been suggested that TP‐induced hepatotoxicity could be copied in a zebrafish model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that TP has antiangiogenic (He et al, ), antiproteinuric (Wang et al, ) and antitumor (Gao et al, ) activities in the zebrafish. It has also been reported that exposure to TP was dose‐dependent for mortality, hepatocyte vacuolation, disarray and oncotic necrosis in zebrafish (Vliegenthart et al, ). It has been suggested that TP‐induced hepatotoxicity could be copied in a zebrafish model.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that TP‐induced hepatotoxicity could be copied in a zebrafish model. Immune response‐associated genes, including nitric oxide synthase, were upregulated, which indicated that activation of the inflammatory signaling pathway might play an important role in TP‐induced hepatotoxicity (Vliegenthart et al, ). However, the roles of apoptosis and autophagy in TP‐induced zebrafish hepatotoxicity were still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…During the last decade, many studies have been carried out to uncover the mechanism of TP‐induced liver injury or hepatotoxicity, particularly at the cellular level. Various new omics technologies, including transcriptomics and metabolomics, have even been adopted (Vliegenthart et al, ; Zhao et al, ). However, the mechanistic explanations for TP‐induced hepatotoxicity still focus on common phenomena or the endpoint events of cell fate, such as oxidative stress, inflammatory reaction, cell cycle arrest and apoptosis (Cao et al, ; Fu et al, ; Meng et al, ; Oliveira et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Emerging data suggested that microRNAs (miRs) were implicated in APAP-or TP-induced liver injury. 31,34 miR-378a-3p was reported to be involved in the pathogenesis of various liver diseases. [35][36][37][38][39] And CYP2E1 is specifically regulated by miR-378a-3p via interactions with the 3′-untranslated regions (3′-UTR) of its mRNA transcript.…”
mentioning
confidence: 99%